Inovasi Penggunaan Media Pembelajaran Berbasis Augmented Reality (AR) Untuk Meningkatkan Hasil Belajar IPAS Siswa Sekolah Dasar - Sheiyla Anggraeni Indayana; Dewi Indrapangastuti (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
This literature review purpose to evaluate the effectiveness of Augmented Reality (AR)-based learning media in improving learning outcomes in Natural and Social Sciences (IPAS) in elementary schools. The problem raised is students' difficulties in understanding abstract concepts due to the minimal use of visual and interactive media. A total of 16 articles from nationally and internationally accredited journals published between 2020 and 2025 were analyzed using content analysis techniques. The results of the study indicate that AR media is consistently able to improve conceptual understanding, learning motivation, and student learning outcomes. This media is also in line with the characteristics of 21st-century learning that emphasizes the integration of digital technology. This study concludes that AR is a promising learning medium to support meaningful and engaging IPAS learning at the elementary school level. This study also recommends further development of AR-based learning models that are contextualized to the characteristics of elementary school students and the national curriculum.Kajian literatur ini bertujuan untuk mengevaluasi efektivitas media pembelajaran berbasis Augmented Reality (AR) dalam meningkatkan hasil belajar Ilmu Pengetahuan Alam dan Sosial (IPAS) di sekolah dasar. Permasalahan yang diangkat adalah kesulitan siswa dalam memahami konsep-konsep abstrak akibat minimnya penggunaan media visual dan interaktif. Sebanyak 16 artikel jurnal terakreditasi nasional dan internasional yang terbit antara tahun 2020–2025 dianalisis menggunakan teknik analisis isi. Hasil kajian menunjukkan bahwa media AR secara konsisten mampu meningkatkan pemahaman konsep, motivasi belajar, dan hasil belajar siswa. Media ini juga sejalan dengan karakter pembelajaran abad ke-21 yang menekankan integrasi teknologi digital. Kajian ini menyimpulkan bahwa AR merupakan media pembelajaran yang menjanjikan untuk mendukung pembelajaran IPAS yang bermakna dan menarik di tingkat sekolah dasar. Kajian ini juga merekomendasikan pengembangan lebih lanjut terhadap model pembelajaran berbasis AR yang kontekstual dengan karakteristik siswa sekolah dasar dan kurikulum nasional.